IMPLEMENTATION OF GRAY LEVEL TRANSFORMATION METHOD FOR SHARPING 2D IMAGES - Jonhariono Sihotang (Sean Institute, 2019)
At present image processing plays an important role, in which the processing does not only provide effects that make an image more artistic but can also improve the quality of the image itself. In the field of photography and film that is used in making animated advertisements on television, or creating effects from dangerous scenes that cannot be done by real humans. Not all digital images have a visual appearance that satisfies the human eye. Dissatisfaction can arise due to interference or lack of maximization of the image quality, such as spots appearing caused by the process of capturing imperfect images, lack of image sharpness due to uneven lighting and resulting in non-uniform intensity, image contrast is too low so objects are difficult separated from the background or interference caused by dirt that adheres to the image.